Brasilacarus cocaris (Acari: Opilioacaridae), a new genus and species from Amazonia, Brazil - Vázquez, Ma. Magdalena; de Araújo, Marcel Santos; Feres, Reinaldo José Fazzio (Zootaxa, 2015)
A new genus and species of Opilioacaridae, Brasilacarus cocaris n. gen., n. sp., is described from adult females and males from Manaus, Brazil. Brief descriptions of damaged tritonymphs and deutonymphs are also provided. The new genus appears to be related to Caribeacarus but possess a unique group of additional strongly modified setae on the tibiotarsus.